Comparison of the effect on Hyperglycemia and the Adverse Effects among Different GLP-1 Receptor Agonists Added to Basal Insulin and between GLP-1 Receptor Agonists and Basal Insulin Versus Basal-Plus or Basal-Bolus Insulin in Type 2 Diabetes: A Meta-Analysis - Manov, Andrey Emanuilov; Hatharasinghe, Ashan Thomas; Lopez, Katrina Equinox (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Diabetes mellitus type 2/ DM2/ - is increasing in incidence in United States and throughout the world mostly due to increasing Obesity epidemy- around 40 % of adult people in USA. Two are the major defects of the disease- insulin resistance which sets up the stage 4-7 years before DM type 2 is diagnosed and relative to the increased resistance insulin deficiency. After the diagnosis of DM type 2 the Insulin resistance stays usually constant while the Insulin deficiency progresses necessitating the intensification of the therapy and eventually the need of Insulin . Initially the insulin is started usually as a basal and eventually as the DM type 2- progresses we add bolus rapid acting insulin to major meal- basal plus regimen/BP/ and eventually to every meal- basal- bolus /BB/ insulin. This intensification of the therapy is frequently able to control DM type 2, but leads to significant 3-4 kg weight gain with risk of hypoglycemia. Other option of intensification of the therapy of DM type 2 is to add to the oral anti - diabetic medications only basal Insulin and GLP1- RAs. GLP1-RAs decrease post prandial blood sugar as the rapid acting insulin does and the long acting GLP1-RAs also decrease fasting blood sugar. GLP1- RAs suppress the appetite and theoretically might lead to weight loss and less incidence of hypoglycemia compare to BP/BB Insulin regimens, because they act on glucose dependent manner- increase the endogenous insulin production only if the blood sugar is elevated. In our meta- analysis our objective was to look at the effect on the blood sugar as well as into looking at the side effect of GLP 1- RAs and basal- Insulin combination compare to BP/BB insulin combination like weight loss/gain, incidence of hypoglycemia, adverse events- mainly the gastrointestinal ones. Our secondary end point was the change in HbA1c between GLP1-RAs and basal insulin group compare to BP/BB insulin group in patients with HbA1c 7-11%. This is the first meta- analysis as far as we now comparing those 2- combinations – BB/BP insulin to GLP1-RAs and basal insulin in the terms of looking as a primary end point at the side effects of those combinations.